Influence of diabetes on survival of patients with glioma: a meta-analysis - Yi, Jing; Wen, Jiangli; Wang, Nianhua; Yuan, Min; Leng, Haibin; Chen, Hua (Frontiers in Endocrinology, 2026)
BackgroundThe prognostic impact of preexisting diabetes on glioma survival remains unclear, with conflicting evidence across studies. This meta-analysis aimed to assess the association between diabetes and survival outcomes in patients with glioma.MethodsWe systematically searched PubMed, Embase, and Web of Science up to April 30, 2025, for cohort studies reporting hazard ratios (HRs) for overall survival (OS) or progression-free survival (PFS) in glioma patients with and without preexisting diabetes. A random-effects model was used to pool multivariate-adjusted HRs accounting for the possible influence of heterogeneity.ResultsTwelve retrospective cohort studies comprising 8,948 patients were included. Eleven studies reported on OS, and four on PFS. Pooled analysis showed that preexisting diabetes was associated with poorer OS (HR: 1.22, 95% CI: 1.10–1.36, p < 0.001; I² = 33%). Sensitivity analysis confirmed result robustness (HR range: 1.18–1.26). Subgroup analyses revealed consistent associations regardless of tumor grade (Grade III–IV: HR: 1.42; GBM: HR: 1.19; p for subgroup difference = 0.47), age (< 60 vs. ≥ 60 years, p = 0.15), sex distribution (< 60% vs. ≥ 60% men, p = 0.91), diabetes type (type 2 vs. overall diabetes, p = 0.33), or follow-up duration (≤ 12 vs. >12 months, p = 0.69). Preexisting diabetes was also associated with poorer PFS (HR: 1.36, 95% CI: 1.01–1.83, p = 0.04; I² = 0%).ConclusionsPreexisting diabetes is associated with reduced survival in glioma patients. These findings highlight the importance of integrating metabolic comorbidities into glioma prognostic assessment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251086248, identifier CRD420251086248.